Recurrent recessive mutation in deoxyguanosine kinase causes idiopathic noncirrhotic portal hypertension. Issue 6 (31st March 2016) - Vilarinho, Sílvia; Sari, Sinan; Yilmaz, Güldal; Stiegler, Amy L.; Boggon, Titus J.; Jain, Dhanpat; Akyol, Gulen; Dalgic, Buket; Günel, Murat; Lifton, Richard P.
Abstract : Despite advances in the diagnosis and management of idiopathic noncirrhotic portal hypertension, its pathogenesis remains elusive. Insight may be gained from study of early‐onset familial idiopathic noncirrhotic portal hypertension, in which Mendelian mutations may account for disease. We performed exome sequencing of eight subjects from six kindreds with onset of portal hypertension of indeterminate etiology during infancy or childhood. Three subjects from two consanguineous families shared the identical rare homozygous p.N46S mutation in DGUOK, a deoxyguanosine kinase required for mitochondrial DNA replication; haplotype sharing demonstrated that the mutation in the two families was inherited from a remote common ancestor. All three affected subjects had stable portal hypertension with noncirrhotic liver disease for 6‐16 years of follow‐up. This mutation impairs adenosine triphosphate binding and reduces catalytic activity. Loss‐of‐function mutations in DGUOK have previously been implicated in cirrhosis and liver failure but not in isolated portal hypertension. Interestingly, treatment of patients with human immunodeficiency viral infection with the nucleoside analogue didanosine is known to cause portal hypertension in a subset of patients and lowers deoxyguanosine kinase levels in vitro ; the current findings implicate these effects on deoxyguanosine kinase in the causal mechanism. Conclusion: Our findings provide new insight into the mechanisms mediating inherited and acquired noncirrhotic portal hypertension, expand the phenotypic spectrum of DGUOK deficiency, and provide a new genetic test for a specific cause of idiopathic noncirrhotic portal hypertension. (Hepatology 2016;63:1977‐1986)